1991
DOI: 10.1139/v91-028
|View full text |Cite
|
Sign up to set email alerts
|

π-Facial stereoselectivity in the Diels–Alder reactions of a rigid carbocyclic diene: spiro(bicyclo[2.2.1]heptane-2,1′-[2,4]cyclopentadiene)

Abstract: . Can. J. Chem. 69, 179 (1991). The plane-nonsyrnmetrical diene spiro(bicyclo[2.2.1]heptane-2,1'-[2,4]cyclopentadiene) (2) was synthesized, and the ITfacial stereoselectivity of its Diels-Alder cycloadditions with three cyclic dienophiles was examined. Adduct ratios were very similar, and the selectivity is surmised to be mainly the result of steric interactions at the transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The stereochemistry of Diels−Alder additions to spiro(bicyclo[2.2.1]heptane-2,1‘-[2,4]cyclopentadiene) and spiro(bicyclo[2.2.2]octane-2,1‘-[2,4]cyclopentadiene) was attributed to the difference in the steric demand of the bridgehead C and the methylene C, corresponding to the isopropyl and ethyl groups, respectively, in the conformations extending their C−H bonds toward the incoming dienophile, Scheme 61 …”
Section: 33 C−c Vs C−c:  Steric Demand Of Rotamers or Electronic Effe...mentioning
confidence: 99%
“…The stereochemistry of Diels−Alder additions to spiro(bicyclo[2.2.1]heptane-2,1‘-[2,4]cyclopentadiene) and spiro(bicyclo[2.2.2]octane-2,1‘-[2,4]cyclopentadiene) was attributed to the difference in the steric demand of the bridgehead C and the methylene C, corresponding to the isopropyl and ethyl groups, respectively, in the conformations extending their C−H bonds toward the incoming dienophile, Scheme 61 …”
Section: 33 C−c Vs C−c:  Steric Demand Of Rotamers or Electronic Effe...mentioning
confidence: 99%
“…McLean and Haynes reported that there was no facial selectivity whatsoever in the reaction of 1 with N -phenylmaleimide, but Mironov stated that, with maleic anhydride, the ratio of anti to syn addition was 12:1. (With other plane−nonsymmetric dienes, N -phenylmaleimide and maleic anhydride have shown negligible differences in facial selectivity. , ) On the other hand, Ford 8 was able to detect only the product of addition syn to the methyl group of 1 when the dienophile was benzyne, and Adam and co-workers 9 indicated that syn addition was the predominant reaction between 1 and 4-methyl-1,2,4-triazoline-3,5-dione. N -Phenylmaleimide, maleic anhydride, and other ethylenic dienophiles all had very similar facial selectivities (about 80% anti addition) in their reactions with 1,2,3,4,5-pentamethyl-1,3-cyclopentadiene ( 2 ), which offers the same facial alternatives as 1 , and Adam's group reported 75% anti addition for 4-methyl-1,2,4-triazoline-3,5-dione with 2 , in contrast with their result with 1 …”
Section: Introductionmentioning
confidence: 99%
“…Compounds 14, 15, and 16 were reheated in benzene and there was no evidence of their equilibration by 1 H NMR spectroscopy. Diene 5 reacted with three ethylenic dienophiles with facial selectivities ranging from 69:31 to 72:28 (at 40°C), once again in favor of addition to the face syn-to-2-H. [11] The facial selectivity for the endo addition of dienophile 7 (69:31), with the preference for addition syn-to-2-H, is remarkably similar to the facial selectivity with 5. This result is also consistent with steric interactions determining the adduct ratios in the endo reactions of 5 and of 7.…”
Section: Resultsmentioning
confidence: 81%
“…The predicted selectivity with 5 is very similar to the experimental ratio of 72:28. [11] Computations involving the plane-nonsymmetric dienophiles 6 and 7 predicted facial selectivities that were less close to experimental values, although, considering only the predicted ratios of the endo adducts, the proportions of the syn-to-2-H adducts were only modestly overestimated. Thus, for 6, the predicted ratio of the endo adducts is 79:21, whereas the experimental result is 89:11; and for 7, the predicted ratio is 60:40, whereas the experimental ratio is 59:41.…”
Section: Computational Chemistrymentioning
confidence: 85%
See 1 more Smart Citation